Defining the QTL for chill requirement during dormancy and dormancy release in apple (Malus x domestica Borkh.). - Cornelissen, Stephanie (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDAgric)--Stellenbosch University, 2021.